2019
DOI: 10.1039/c9cp02397f
|View full text |Cite
|
Sign up to set email alerts
|

Chain length effect on thermal transport in amorphous polymers and a structure–thermal conductivity relation

Abstract: The physics of thermal transport in polymers is important in many applications, such as in heat exchangers and electronics packaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 51 publications
7
61
0
Order By: Relevance
“…Several molecular dynamics studies on polyethylene melts have found that λ increases with M with a similar dependence to that found on the experimental results by Hansen et al [11]. However, the increase in λ is limited to low molecular weights [18,19,20], and all the mentioned simulation studies showed deviations from the proposed N 1/2 model, with a plateau in λ over the critical molecular weight or chain length limit N c = 2N e . Unfortunately, the range of molecular weights covered by these simulations did not correspond to those investigated experimentally [11] due to the computational cost required to equilibrate large molecular weight polymeric melts.…”
Section: Introductionsupporting
confidence: 77%
“…Several molecular dynamics studies on polyethylene melts have found that λ increases with M with a similar dependence to that found on the experimental results by Hansen et al [11]. However, the increase in λ is limited to low molecular weights [18,19,20], and all the mentioned simulation studies showed deviations from the proposed N 1/2 model, with a plateau in λ over the critical molecular weight or chain length limit N c = 2N e . Unfortunately, the range of molecular weights covered by these simulations did not correspond to those investigated experimentally [11] due to the computational cost required to equilibrate large molecular weight polymeric melts.…”
Section: Introductionsupporting
confidence: 77%
“…It can be expected that PBD200k, because of its longer chain length and therefore more unsaturation compared to PBD5k chain, is more susceptible to thermo-oxidative degradation. It has also been established before that increasing chain length in polymers leads to an increase in thermal conductivity [31], and increased thermal conductivity has been linked before to increased droplet combustion rates [17]. Also, due to easier C-C bond scission in longer chain polymers compared to short chain polymers, PBD200k is more susceptible to thermal degradation compared to PBD5k [32].…”
Section: Resultsmentioning
confidence: 94%
“…[6][7][8][9] A number of recent studies have revealed that polymer thermal conductivity is strongly related to its molecular level conformation. 6,8,[10][11][12][13][14] For example, stiffer molecular backbones can make the chains straighter even in the amorphous state 15 and thus increase the amount of heat that can be transferred through the strong backbone. 12 In polymer blends, it is reported that increasing the inter-chain interaction through engineering hydrogen bonds can stretch the polymer chains and enhance the thermal conductivity up to 1.5 W/(m.K).…”
Section: Introductionmentioning
confidence: 99%